A influência de aspectos contextuais e individuais na saúde bucal de adultos do Rio Grande do Sul: um estudo multinível - Koltermann, Annie Pozeczek (Universidade do Vale do Rio do Sinos, 2008)
Oral functionality has important role in maintaining masticatory capacity. This can be achieved with the presence of at least 20 functional teeth in mouth. The objective of this study was to investigate the effect of individual and contextual factors on the functional dentition status of Brazilian adults.
Keywords: adultos; desigualdades em saúde; estudo transversal; saúde oral; dentição funcional; adult; health inequalities; oral health; oral functionality; Ciências da Saúde